PEMBUATAN KOMPOS DARI LIMBAH PADAT (SLUDGE) PABRIK PULP DAN PAPER - Maria Peratenta Sembiring; Rozanna Sri Irianty (Universitas Andalas, 2012)
One of the method to use pulp and paper mill sludge was convert it become a compost. This research result showed that time variation of compost have different physical and organic matter properties. In physical properties, 3 months of compost had 12.57% moisture content, while organic matter contain 10.56% carbon, 1.07% nitrogen, and 9.87 C/N ratio. For 4 months compost had 6.79% moisture content, 11.88% carbon, 0.91% nitrogen, and 13.05 C/N ratio. Nutrients content from both composts appropriate with the standard value of National Standarisation Body.